2020
DOI: 10.1007/s11665-020-04998-1
|View full text |Cite
|
Sign up to set email alerts
|

A New Design for Friction Stir Spot Joining of Al Alloys and Carbon Fiber-Reinforced Composites

Abstract: Friction stir spot welding (FSSW) has been recently developed to join dissimilar materials. However, the traditional requirement for a rotating tool consists of a pin and shoulder in FSSW leads to a complex joining process and unpredictable defects. In this study, a new static-shoulder design in FSSW was proposed and developed to join Al alloys to carbon fiber-reinforced polymer (CFRP) composites. The main joining parameters, including pin rotational speed, pin feed rate and pin plunge depth, were varied to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Refill FFSW, even though it gives an improved weld strength compared to FFSW, is considered an expensive and complex process, as the tool has three separate components that need to be controlled [150]. In FFSW, the reduced weld strength is mainly due to weld thinning, keyhole defects, and hook defects [151,152]. Other variations in the FFSW techniques reported for joining metal-polymer composite joints are threaded hole friction stir spot welding (THFSSW) [153,154], static shoulder friction stir spot welding (SSFSSW), and pinless friction stir spot welding (PFSSW) [151,155].…”
Section: Advantages and Drawbacks Of The Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Refill FFSW, even though it gives an improved weld strength compared to FFSW, is considered an expensive and complex process, as the tool has three separate components that need to be controlled [150]. In FFSW, the reduced weld strength is mainly due to weld thinning, keyhole defects, and hook defects [151,152]. Other variations in the FFSW techniques reported for joining metal-polymer composite joints are threaded hole friction stir spot welding (THFSSW) [153,154], static shoulder friction stir spot welding (SSFSSW), and pinless friction stir spot welding (PFSSW) [151,155].…”
Section: Advantages and Drawbacks Of The Processesmentioning
confidence: 99%
“…In FFSW, the reduced weld strength is mainly due to weld thinning, keyhole defects, and hook defects [151,152]. Other variations in the FFSW techniques reported for joining metal-polymer composite joints are threaded hole friction stir spot welding (THFSSW) [153,154], static shoulder friction stir spot welding (SSFSSW), and pinless friction stir spot welding (PFSSW) [151,155]. Studies on RSW, FSSW, PFSSW, and THFSSW (at times referred to as pre-hole FSSW (PHFSSW)) have shown that FFSW gives a better weld strength and has more flexibility in joining aluminum alloys and polymer composites yet is far more expensive compared to RSW, as shown in Figure 21 below.…”
Section: Advantages and Drawbacks Of The Processesmentioning
confidence: 99%
“…139 A static shoulder FSpJ tool with a fluted tool increased the mechanical interlocking of the Al-CFRP joint. 140 FSSW used a hybrid HCl immersion and salinization treatment to generate a high-strength Al/ CFRTP joint. Dendritic nanostructures were created by immersing an Al surface in HCl, resulting in mechanical interlocking and enhanced wettability.…”
Section: Newly Developed Strategies To Enhance Materials Characteristicsmentioning
confidence: 99%
“…The resulting joints are responsible for ensuring effective load transfer between parts, thus maintaining the integrity of the linked components [ 46 ]. For composites, there are two main joining methods: mechanical fastening (which infers undesired and prejudicial stress concentration spots and an overall weight increase caused by additional fasteners [ 47 ]) and adhesive bonding (which provides load transfer with more uniform distribution over larger areas) [ 48 ]. Adhesive bonding may be performed by secondary bonding, involving the usage of adhesives between the parts [ 49 , 50 ], or by co-curing, where the matrix of the composite is cured in contact with the desired adherend and, hence, cure and bonding happen simultaneously.…”
Section: Introductionmentioning
confidence: 99%